Biologic drugs in hidradenitis suppurativa: what does the GP have to know? A narrative review - Mendes-Bastos, Pedro; Benhadou, Farida; Venturini, Marina; Molina-Levya, Alejandro; Thomas, Nicolas; Alarcon, Ivette; Bechara, Falk G. (Frontiers in Medicine, 2024)
Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease with a profound disease burden. In recent years, the advent of biologic therapies has improved the treatment landscape for patients with moderate to severe HS. In this new therapeutic era, the role of the general practitioner (GP) in HS treatment is becoming more important than ever. This review discusses how to recognize and diagnose HS by detailing common symptoms. HS can also present with multiple comorbidities. The GP's role in screening for and treating these important comorbidities is pivotal. This review highlights the HS treatment landscape, with a specific focus on what the GP can recommend. The three approved biologics for treating HS include adalimumab, secukinumab and bimekizumab; the benefits and concerns of biologics in everyday clinical practice are detailed. In summary, this review serves as a HS management guide for GPs, with a particular focus on the biologic treatment landscape.